Developmental level of black first-year nursing students - Paula P du Rand; Marlene J Viljoen (AOSIS, 2000)
Black first-year nursing students hailing from a historically disadvantaged education situation may experience various problems at the university. It is therefore important to support these students. If however, it should prove possible to determine the exact nature of the backlogs in their development, the lecturer would be able to offer meaningful support. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.